THE INFLUENCE OF PRICE PERCEPTION, ADVERTISING PERCEPTION, AUDIO QUALITY PERCEPTION, MUSIC DOWNLOAD PERCEPTION, AND UNLIMITED SKIP PERCEPTION ON THE DECISION TO USE SPOTIFY PREMIUM APPLICATION - Azzahira Putri Zakaria, Grandhis; Pradekso, Tandiyo; Ratri Rahmiaji, Lintang (Interaksi Online, 2024)
This study aims to explain the influence of price perception, advertising perception, audio quality perception, music download perception, and unlimited skip perception on the decision to use Spotify Premium application. This research is quantitative research, with the theory used in this research are Theory of Planned Behavior and Marketing Mix Strategy Concept which uses a non-probability sampling technique with purposive sampling. The total number of respondents selected was 106 respondents, lived in Semarang city, aged 18 to 35 years, and used Spotify application. The result of testing the first hypothesis using simple regression linear analysis shows that there is an influence of price perception on the decision to use Spotify Premium application with a significance value of 0,000 means very significant. Meanwhile, the second hypothesis using multiple linear regression analysis shows that there is no influence of advertising perception, audio quality perception, music download perception, and unlimited skip perception on the decision to use Spotify Premium application with a significance value of 0,234 means not significant. However, if viewed partially, music download perception variable has an influence on the decision to use Spotify Premium application with a significance value of 0,048 means significant. The recommendation given to future researchers is that more comprehensive research is needed using other variables that can influence the decision to use Spotify Premium application.